Activated carbon from honeydew rind as an adsorbent in zinc removal from aqueous solutions - Yunus, Zalilah Murni; Othman, Norzila; Hamdan, Rafidah; Ruslan, Nurun Najwa; Abu Kasin, Norfarihah; Leman, Nur Solini
"This study focusing in producing activated carbon (AC) from honeydew rind, a low-cost agricultural by-product, by chemical activation using H2SO4 used as an adsorbent for the removal of zinc ions from aqueous solutions. Preparation method on the effect of surface morphology at different carbonization temperatures 450oC, 470oC, 490oC and 510oC was studied. The AC was characterized using FEM-SEM, FTIR and TG. Batch adsorptions were carried out to optimize different variables such as zinc concentration, contact time, pH and biosorbent amount. AAS analysis showed that the maximum adsorption of zinc onto honeydew rind AC was achieved at the conditions of pH 7.5, 1.5g biosorbent amount, 1000mg/L initial zn concentration and 45min contact time. The maximum metal uptake and maximum removal were 66.55mg/g and 99.79% respectively."